Survival status and predictors of mortality among patients admitted to surgical intensive care units of Addis Ababa governmental hospitals, Ethiopia: A multicenter retrospective cohort study - Endeshaw, Amanuel Sisay; Fekede, Mulualem Sitot; Gesso, Ashenafi Seifu; Aligaz, Esubalew Muluneh; Aweke, Senait (Frontiers in Medicine, 2023)
Introduction: Critical care is a serious global healthcare burden. Although a high number of surgical patients are being admitted to the surgical intensive care unit (SICU), the mortality remained high, particularly in low and middle-income countries. However, there is limited data in Ethiopia. Therefore, this study aimed to investigate the survival status and predictors of mortality in surgical patients admitted to the SICUs of Addis Ababa governmental hospitals, Ethiopia. Methods: A multicenter retrospective cohort study was conducted on 410 surgical patients admitted to the SICUs of three government hospitals in Addis Ababa selected using a simple random sampling from February 2017 to February 2020. The data were entered into Epidata version 4.6 and imported to STATA/MP version 16 for further analysis. Bi-variable and multivariable Cox regression models were fitted in the analysis to determine the predictor variables. A hazard ratio (HR) with a 95% confidence interval (CI) was computed, and variables with a P value < 0.05 were considered statistically significant. Results: From a sample of 410 patients, 378 were included for final analysis and followed for a median follow-up of 5 days. The overall mortality among surgical patients in the SICU was 44.97% with an incidence rate of 5.9 cases per 100 person-day observation. Trauma (AHR= 1.83, 95% CI: 1.19-2.08), Glasgow coma score (GCS) <9 (AHR= 2.06, 95% CI: 1.28-3.31), readmission to the SICU (AHR= 3.52, 95% CI: 2.18-5.68), mechanical ventilation (AHR= 2.52, 95% CI: 1.23-5.15), and creatinine level (AHR= 1.09, 95% CI: 1.01-1.18) were found to be significantly associated with mortality in the SICU. Conclusion: The mortality of surgical patients in the SICU was high. Trauma, GCS <9 upon admission, readmission to the SICU, mechanical ventilation, and increased in the creatinine level on admission to the SICU were the identified predictors of mortality in the SICU.